Iron and Arsenic Speciation and Distribution in Organic Flocs from Streambeds of an Arsenic-Enriched Peatland - ThomasArrigo, Laurel; Christian Mikutta; James Byrne; Kurt Barmettler; Andreas Kappler; Ruben Kretzschmar (My University, 2014)
Iron-rich organic flocs are frequently observed in surface waters of wetlands and show a high affinity for trace metal(loid)s. To date, spectroscopic speciation analyses of Fe and trace elements in these mineral-organic matter (OM) associations are missing. In this study, we investigated the speciation and distribution of Fe and As in flocs collected from low-flow streams (pH 5.3–6.3) of the naturally As-enriched peatland Gola di Lago (Switzerland) using 57Fe Mössbauer spectroscopy and synchrotron X-ray techniques. The flocs were rich in acid carbohydrates and contained up to 22.1 wt % Fe, 34.9 wt % C, and 2620 mg/kg As. Mössbauer analyses revealed small quantities (<5%) of Fe(II) and Fe(III)-OM complexes and the predominance of ferrihydrite (∼Fe5HO8·4H2O, 51–59%) and lepidocrocite (γ-FeOOH, 34–46%). The latter was not observed by synchrotron X-ray diffraction, implying a coherent scattering domain size of <10 nm. Iron X-ray absorption spectroscopy (XAS) confirmed the Mössbauer results, and bulk As XAS indicated the prevalence of arsenate (71–84%) in the flocs. Shell-fit analyses showed that As was entirely sorbed to Fe(III)-(oxyhydr)oxides and that both arsenate and arsenite exclusively formed monodentate-binuclear (“bridging”) complexes (RAs–Fe = 3.31–3.34 Å). Microfocused X-ray fluorescence spectrometry documented a strong correlation between As and Fe in the flocs. These analyses also revealed intense As hotspots coinciding with abundant freshwater green algae (Closterium spp.). Microfocused As X-ray absorption near-edge structure spectra collected at algae-specific points identified up to 29% As(III), which, in combination with ∼5% As(III) detected at Fe-rich points, suggests As(V) bioreduction in the algae. Our findings imply that floc (bio)organics serve primarily as nucleation sites for the precipitation of nanocrystalline Fe(III)-(oxyhydr)oxides, rendering flocs effective sorbents for trace metal(loid)s. Thus, Fe-rich freshwater flocs likely play a pivotal role for the speciation and cycling of trace elements in wetlands.
Keywords: Elements; Extended X-ray absorption fine structure; Minerals; Natural resources; Scattering